Aposentadoria da pessoa intersexo segurada do Regime Geral de Previdência Social - Terto Junior, Luciano Lavor (2025)
This dissertation aims to tackle the effectiveness of the current Brazilian social security system in relation to intersex people, debating the need and/or possibility of adopting differentiated requirements or criteria for granting social security benefits in favor of intersex insured people. Social security, as a subsystem of social security, is a fundamental instrument of the welfare state, guaranteeing social and individual rights. Thus, while the urgency, timeliness and importance of studies focused on the rights of the intersex community is clear, the study focused on social security makes it possible to analyze the inclusion of these people within the system of defense and guarantee of social rights, and also the social preparation of the State in dealing with the specific social demands of this group. The dissertation started from the hypothesis that the Brazilian social security system is not prepared to provide effective social security for intersex people, and therefore requires the creation of differentiated requirements or criteria for granting social security benefits to intersex insured people. In order to investigate the veracity of the above, qualitative, bibliographical and analytical research was used, as well as a fusion of methods, with Descartes' deductive method standing out if the work is taken as a whole, starting from general ideas, in order to finally reach a conclusion on the specific issue. The hypotheses were confirmed and further explored, so that it is concluded that it is necessary to create differentiated criteria for access to pensions for intersex insured people